Photolysis of parabens using medium-pressure mercury lamps: Toxicity effects in MCF7, Balb/c 3T3 cells and Ceriodaphnia dubia. (October 2018) - Gomes, Francisco E.R.; Bergo, Patricia L.S.; Trap, Marília A.; Spadoto, Mariângela; Galinaro, Carlos A.; Rodrigues-Filho, Edson; Leitão, Andrei; Tremiliosi-Filho, Germano
Abstract: Degradation studies of the propylparaben (PrP), butylparaben (BuP) and of the propylparaben-butylparaben mixture (PrP-BuP) in deionized water and surface river water was investigated as a function of pH and initial concentration of the reactants using a medium-pressure mercury lamp. The photolysis of parabens (concentration ranging from 5 to 30 mg L −1 ) followed apparent pseudo-first-order kinetics, with rate constants ( k ) in deionized water and surface river water changed from 1.80 × 10 −1 to 3.68 × 10 −2 min −1 and 1.43 × 10 −1 to 1.45 × 10 −2 min −1, respectively. Degradation reaction was faster at pH 5 in comparison with pH 7 or 11. The photolysis of parabens was greater than 91%, with low mineralization (26.15%) observed in acidic medium after 95 min. Analysis by chromatography coupled to mass spectrometry (LC-MS/MS) showed that only one product was generated during the degradation reaction and has UV bands similar to 3, 4-dihydroxybenzoic acid. Estrogenic activity tests showed that non-degraded parabens stimulated the growth of breast adenocarcinoma (MCF-7) cells and this effect was evaluated after the photolysis. Cytotoxicity assays using fibroblasts cells (Balb/C 3T3 clone A31) indicated that the parental compounds and degradation products were not cytotoxic. On the contrary, non-degraded parabens were toxic to Ceriodaphnia dubia, but the product of photolysis was not. Overall, the photolytic method presented was able to degrade these parabens providing safe and non-estrogenic reaction product. Graphical abstract: Image 1 Highlights: Photolysis could be adequate for parabens, since produce inactive by-products. Parabens induce estimulation MCF-7 cell growth, being BuP the most potent one. Photolysis on PrP, BuP and Mix solutions could reduce toxicity for Ceriodaphnia dubia.